1986
DOI: 10.1002/polb.1986.090240908
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of a phase‐separated and a molecular composite PBT/ABPBI polymer blend

Abstract: The structure and morphology of homopolymers and blends of rigid‐rod poly(p‐phenylene benzobisthiazole) (PBT) and semiflexible coil poly[2,5(6)benzimidazole] (ABPBI) were examined by wide‐angle x‐ray diffraction and scanning and transmission electron microscopy. When samples were processed from a solution where the total polymer concentration of 30% PBT/70% ABPBI blend was greater than a critical concentration, large‐scale phase separation occurred and 0.1–4 μm ellipsoidal particles were present in a ductile m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…ABPBI has been shown to be crystalline,14–16 but the X‐ray data contain relatively few Bragg reflections. Wereta et al14 reported that films of ABPBI prepared from FAMC and MSA solutions had uniplanar orientation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ABPBI has been shown to be crystalline,14–16 but the X‐ray data contain relatively few Bragg reflections. Wereta et al14 reported that films of ABPBI prepared from FAMC and MSA solutions had uniplanar orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Wereta et al14 reported that films of ABPBI prepared from FAMC and MSA solutions had uniplanar orientation. Hwang et al15 prepared oriented fibers from MSA/chlorosulfonic acid solutions and interpreted the X‐ray data in terms of a 2 1 chain conformation with a fiber repeat of c = 11.5 Å. Krause et al16 observed off‐axis layer line reflections pointing to the existence of three‐dimensional order and proposed an orthorhombic unit cell for ABPBI, with the dimensions a = 7.16 Å, b = 3.49 Å, and c = 11.7 Å, by analogy to the structures of poly(2,5‐benzoxazole) (ABPBO) and poly(2,6‐benzothiaole) (ABPBT) 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were heat‐treated at a temperature of 100 and 250 °C (5 h each) prior to recording the XRD patterns; the tests were carried out on the same sample in each case, and after the annealing at 250 °C, the XRD pattern was again recorded at 30 °C (30 °C—after HT, Figure ). The undoped samples [Figure (a,b)] show distinct peaks at 2θ values of 10 and 26.5° attributed to the orthorhombic unit cell of ABPBI . The broad shoulder peak observed at 2θ value of 18.5° can be attributed to short‐range order in the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of a small amount of flexible coil molecules into the rigid-rod matrix has been sought as a route for improving the compressive strength of the highly oriented rigid-rod materials (2)(3)(4)(5)(6)(7)(8)(9). On the other hand, a minor amount of rigid-rod polymer molecules may be dispersed in the matrix of flexible coils in order to reinforce the matrix (7). This concept is similar to the principle of the chopped fiber reinforced composites (10,11), except that reinforcement is expected to occur at a molecular level or a nanometer-scale.…”
mentioning
confidence: 99%